Natural product-inspired profluorophores for imaging NQO1 activity in tumour tissues. Issue 17 (1st September 2019) - Cheng, Zhiming; Valença, Wagner O.; Dias, Gleiston G.; Scott, Jamie; Barth, Nicole D.; de Moliner, Fabio; Souza, Gabriela B.P.; Mellanby, Richard J.; Vendrell, Marc; da Silva Júnior, Eufrânio N.
Graphical abstract: Abstract: Herein we designed a collection of trimethyl-lock quinone profluorophores as activity-based probes for imaging NAD(P)H:quinone oxidoreductase (NQO1) in cancer cells and tumour tissues. Profluorophores were prepared via synthetic routes from naturally-occurring quinones and characterised in vitro using recombinant enzymes, to be further validated in cells and fresh frozen canine tumour tissues as potential new tools for cancer detection and imaging.